1985
DOI: 10.1042/cs0690673
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hypoglycaemia on visual function: a clinical and electrophysiological study

Abstract: Disturbance of vision commonly accompanies hypoglycaemia. This study was designed to investigate the nature of the visual disturbance, the blood glucose threshold at which the disturbance occurred and the physiological basis. Measurements were made of the corrected visual acuity, colour vision (100 Hue test), visual evoked potentials (VEP), electroencephalography (EEG) frequency analysis and psychometry (digit recall) during stepwise induction of controlled hypoglycaemia produced by an intravenous insulin infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 0 publications
4
40
1
Order By: Relevance
“…This conflicts with the results of another study, which failed to show any effect of moderate hypoglycemia (venous blood glucose 2.4 mmol/liter) on VEP latency in nondiabetic subjects (61). Concurrent EEG changes were observed in both studies (57,61) with an increase in slow waves (␦-and -bands) at the expense of fast ␣-waves, particularly in the frontal regions of the brain. (64)].…”
Section: P100 and Hypoglycemiacontrasting
confidence: 54%
See 1 more Smart Citation
“…This conflicts with the results of another study, which failed to show any effect of moderate hypoglycemia (venous blood glucose 2.4 mmol/liter) on VEP latency in nondiabetic subjects (61). Concurrent EEG changes were observed in both studies (57,61) with an increase in slow waves (␦-and -bands) at the expense of fast ␣-waves, particularly in the frontal regions of the brain. (64)].…”
Section: P100 and Hypoglycemiacontrasting
confidence: 54%
“…Several studies have shown no change in corrected visual acuity during acute hypoglycemia (57, 58) despite a fall in intraocular pressure (59) and a reduction in volume and depth of the anterior chamber of the eye (60). Measurement of VEPs during acute hypoglycemia (venous blood glucose levels below 2.5 mmol/liter) has demonstrated prolongation of the P100 latency, which did not differ significantly between diabetic and nondiabetic subjects (57). This conflicts with the results of another study, which failed to show any effect of moderate hypoglycemia (venous blood glucose 2.4 mmol/liter) on VEP latency in nondiabetic subjects (61).…”
Section: P100 and Hypoglycemiamentioning
confidence: 99%
“…In some studies (6,7,9,16,17), memory functions were impaired during acute hypoglycemia, whereas in other studies (8,18,19), memory was apparently unaffected. Variability of results may relate to methodological differences.…”
mentioning
confidence: 98%
“…The reduction in relative CMG uptake identified in regions of occipital cortex and cerebellum probably reflects deactivation of these regions during hypoglycaemia. The occipital cortical region is centred on the striate visual cortex, con-cerned with primary visual processing, and colour vision and visual discrimination are known to be impaired during hypoglycaemia [51]. Similarly, impairment in function of the cerebellar vermis may lead to decrement, not only in motor function and coordination, but in cognitive, predominantly executive, processes [52].…”
Section: Discussionmentioning
confidence: 99%